Meet the man who turns vission into mission. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2008)
More and more universities are committed to taking the bilateral relationship with the industries to higher and more comprehensive level. Universiti Putra Malaysia (UPM) too has taken initiative to join the league to boost its professionalism, networking and educational opportunities. Over the years. UPM has undergone phases of extensive development starting from the transformation of Serdang School of Agriculture in 1931 to Universiti Pertanian Malaysia in 1969 as well as to Universiti Putra Malaysia (1997). Along the way, UPM has pinned its vision to become a world-class university. This implies that UPM needs to increase its effort to rise to a much higher level; its core business on teaching and learning, research and innovation and professional services. Hence, greater linkages between UPM and industries will be a crucial enabler to this end. In line with this, the creation of the new portfolio of the Deputy Vice Chancellor (Industry and Community Relations) by the Ministry of Higher Education Malaysia (MoHE) in UPM in late 2007 can be viewed as a remarkable effort of MoHE to strengthen the university-industry linkages.